Thermodynamic evaluation and molecular dynamic simulation of thermostable lipase from ; Bacillus stearothermophilus PI, Bacillus stearothermophilus LI and Geobacillus stearothermophilus Strain TI - Abdul Rahman, Mohd Basyaruddin; Abedikargiban, Roghayeh; Basri, Mahiran; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Abdul Wahab, Habibah; Jacobs, Donald (2007)
Structural of thermostable enzyme offers insightninto mechanisms used to enhance thermal stability which may be of commercial value in engineering lipases for industrial purpose. In order to examine the factors which have been considered for protein thermostability, a longscale Molecular Dynamic (MD) simulation were performed in a group of three thermostable lipases; Bacillus stearotthermophilus PI lipase (PDB entry IJB), Bacillus stearothermophilus LI lipase (pDB entry 1KUO), and Geobacillus sp. Strain T1 lipase (PDB entry 2DSN) which are in a very high homology (more than 90%). Each stryycture consists of two chains with 388 amino acids (43 kDa) in each chain in a closed confirmation. The significance of these structures is a zinc-binding site which is unique among all lipases. There is yet no universal theory or rule to explain the principles underlying protein thermo stability and it appears to be interplayed by many factors. By this, along MD production were performed from 0 to 375 K in four continuous and separate but procedurally identical simulations in a total of 4.0 ns for each structure at 300,325,350 & 375 K. All the trajectories generated have been used for analyses in order to provide a framework of protein thermo stability. We compared salt bridges, ionic networks, hydrogen bonds, solvent accessible surface area, root means square deviations, & root mean square fluctuations among the structures in order to study the thermostability mechanism employed in these group of homolog protein with the aim of finding how protein structure and dynamics are affected by elevated temperatures.